2016
DOI: 10.1002/ddr.21291
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxic Evaluation of Monocarbonyl Analogs of Curcumin as Potential Anti‐Tumor Agents

Abstract: Preclinical Research A series of mono‐carbonyl curcumin analogs with different substituents at the 4/4’‐position of the phenyl group were synthesized and screened for in vitro cytotoxicity against a panel of human cancer cell lines using a methyl thiazolyl tetrazolium assay. Several of the curcumin analogs, especially B114, exhibited a wide‐spectrum of anti‐tumor properties in all tested cell lines, indicating their potential in as anti‐cancer lead compounds. Further toxicity testing in the NRK‐52E kidney cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The curcumin-like diarylpentanoid skeleton derivatives have been reported to exhibit a wide range of bioactivities, including antioxidant, anticancer, anti-inflammation, anti-melanogenesis, and anti-tyrosinase [ 13 , 14 , 15 , 16 , 17 , 18 ] activities. Especially, Leow et al [ 19 ] reported in 2014 that dibenzylidene-cyclopentanone scaffolds, including (2 E ,5 E )-2,5-bis(3-hydroxy-4-methoxybenzylidene)cyclopentanone (BHCP) ( Figure 1 ), might contribute to the protective effects on human osteosarcoma via regulation of the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The curcumin-like diarylpentanoid skeleton derivatives have been reported to exhibit a wide range of bioactivities, including antioxidant, anticancer, anti-inflammation, anti-melanogenesis, and anti-tyrosinase [ 13 , 14 , 15 , 16 , 17 , 18 ] activities. Especially, Leow et al [ 19 ] reported in 2014 that dibenzylidene-cyclopentanone scaffolds, including (2 E ,5 E )-2,5-bis(3-hydroxy-4-methoxybenzylidene)cyclopentanone (BHCP) ( Figure 1 ), might contribute to the protective effects on human osteosarcoma via regulation of the Wnt/β-catenin signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[21] MAC have attracted considerable attention because they feature greater stability than Curcumin, thus retaining or even increasing biological activity, while also improving pharmacokinetics. Interesting results have been reported in particular for MAC anti-inflammatory, [22] and anticancer activity, [23][24][25][26] (e.g., anti-prostate, [27,28] -breast, [29] -gastric [24,30] and -non-small-cell lung cancer [31][32][33]). A cell-apoptosis mechanism that is induced by endoplasmic reticulum stress has been hypothesised to explain these latter properties.…”
Section: Introductionmentioning
confidence: 99%
“…Also, compound i exhibited remarkable effects on anti‐proliferative activity and EGFR TK inhibitory activity . In 2016, Xu and co‐workers reported (2 E ,5 E )‐2,5‐bis(4‐[2‐hydroxyethoxy]‐3‐methoxybenzylidene)cyclopentanone ( j ), which showed potent cytotoxicity against human osteosarcoma cell lines U2‐OS and OS‐732, prostate cancer cell line PC‐3, and mouse mastocytoma cell line P815, implying their specific potential in the chemotherapy of cancer . Furthermore, Cheng and co‐workers introduced compound k as a coactivator‐associated arginine methyltransferase 1 (CARM 1) inhibitor .…”
Section: Introductionmentioning
confidence: 99%